An investigation of the factors that influence Grahamstown East grade 12 learners to aspire to higher education : a case study - Burns-Ncamashe, Zimasa Nomsawezulu Ancilla (Rhodes University, Faculty of Education, Department of Education, 2005)
This research is an investigation into the factors that influence the decisions of grade 12 learners from Grahamstown East disadvantaged communities to pursue higher education. Research on learner aspirations has largely focused on access to higher education and little or no attention has been has been paid to the enabling or limiting factors and what can be done to increase the numbers of learners from disadvantaged communities who enrol at higher education institutions. This study aims to fill that gap. The research was a qualitative case study located in the interpretive paradigm. The data was gathered using questionnaires and focus group interviews for grade 12 learners. Individual interviews were conducted with the parents of the grade 12 research participants, educators and the school management team. Observation and documentary evidence from school documents were also used for data collection. The data were analysed using systematic patterning, were interpreted, and given meaning linking it to the literature surveyed. The main findings indicate that a number of enabling factors that influence grade 12 learners to pursue higher education co-exist with limiting factors. Recommendations arising from the main findings are presented and the limitations of the research are identified. Areas for possible further research in strengthening learner support so as to increase the numbers of learners who qualify for higher education and to enable the learners from disadvantaged communities to realise their aspirations, are suggested.
Keywords: Education -- South Africa -- Grahamstown -- Case studies; Education, Secondary -- South Africa -- Grahamstown -- Case studies; Education, Higher -- South Africa -- Grahamstown -- Case studies; Student aspirations -- South Africa -- Grahamstown -- Case studies; High school graduates -- South Africa -- Attitudes -- Case studies; Vocational interests -- South Africa -- Grahamstown -- Case studies